Notes on censorship under the Estado Novo regime in Portugal: the case of História do Barba Azul from Livraria Civilização - Diana Maria Martins (Bellaterra Journal of Teaching & Learning Language & Literature)
The action of the censorship apparatus was legally institutionalized in Portugal during the dictatorial regime. The goal of this concise study is to recognize two versions of the story of Bluebeard which were published in 1954 and 1956. These two versions, called História do Barba Azul, were part of “Coleção Carochinha”, a series of traditional short stories. We will therefore seek to show that “a posteriori censorship” (Machado, 2015) took place during a process of seizure by the political police, PIDE. To legitimize the seizure of the volume under analysis, it was stated that it had not been revised by the CLEM, according to the document on the disciplinary process 1/8, from April 25th, 1955. It was pointed out that the story of Bluebeard (História do Barba Azul), was the only one in the collection that would remain seized, and any future publication of this story would continue to be forbidden.